Desempenho de novos produtos: o caso do pão de queijo forno de Minas - Carvalho, Helton Pinheiro de (2001)
The twenty-one century starts and bring together a period of transformation that have never seen before; technology of information, opening of markets and micro informatic, between others factors, speed up the changes, became the environment largely competitive and demand that enterprises become quick and continuai in the innovation process and improvementofyour products. Fomo de Minas bread cheese is a clear case ofproduct development, that innovate and consolidate in the market. This product, in ten years of existence, reached out a big improvementofmarket share, making it attractive to national and foreign enterprises. This research have as objective, describe Fomo de Minas bread cheese development process, the environment of enterprise, identify the consumer perception about the product, and relate the factors linked to its success. To make that, a qualitative study of case was done, using individual interview with consumers and owners of the organization. Afler analysed, the results were related with reviewed literature, allowing it reachs out the objectives of research. The results have shownthat the condition of demand and the big competition that enterprise have met, since its first days, were aspects that improved its development. Other aspects like sources of supplies and suppliers competitiviness, became a competitive advantage, but afler enterprise growth. The development process had multidiscipliners teams, with strong leadership and flexibility. It must either, emphasize the various aspects linked to productconcept,that are perceived by consumers like the main benefit and gap towards competitors. Further, the big product market share reached out have shown us the success of comercial strategy used by the enterprise. New products developments must emphasize and looking for market oriented concepts, reaching out an comtemporary pattern and continuai improvement. This must be reached out centralizing the efforts around the project, narrow clients relationship, and using correct marketing tools. Finaly, the efficience in process is not enough, the environment where will be installed the factory is a very important aspect and must rank, trying to get attributes that improve the enterprise development and competitiviness in the worldwide market.